Wenecja Aleksandra Błoka w tłumaczeniu Kazimierza Wierzyńskiego. Refleksje na temat przekładu - Frajlich, Anna (Tematy i Konteksty, 2020)
The article provides a comparative interpretation of the poem Венеция by Aleksander Błok and its Polish translation by Kazimierz Wierzyński. According to the author of the article, both poetical devices of the original and its main topics and motifs – although modified to some extent in the translation process – have been replaced in the translation by semantic and stylistic equivalents that not only successfully represent artistic values of the source text in the view of the Polish readers but also additionally emphasize a variety of the textual elements vital for its poetical significance and literary value.